A new method for measuring the flatness of large and thin silicon substrates using a liquid immersion technique. (9th October 2015) - Liu, Haijun; Dong, Zhigang; Huang, Han; Kang, Renke; Zhou, Ping
Abstract: Flatness measurements of thin and large substrates are greatly affected by gravity. In this work, a new method was proposed for accurately measuring the flatness error of large and thin silicon wafers using a floating technique. In this method, a silicon wafer was immersed in a liquid that had a density slightly lower than that of silicon and was supported by three ball supporters in the liquid. The wafer shape was measured using a laser triangulation sensor. The buoyancy force on the wafer inside the liquid could cancel out most of the effect of gravity. The residual effect of gravity was further removed by subtracting the residual deflection calculated by finite-element modeling from the measured result. The method was validated by comparing the flatness values of a thick wafer measured using this method and via a commercially available interferometer. The deformations of wafers ground by #600 and #2000 diamond wheels were measured and the measurement error was less than 3% of the total deformation.